2021
DOI: 10.1111/hepr.13597
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of therapeutic outcomes of sorafenib and lenvatinib as primary treatments for hepatocellular carcinoma with a focus on molecular‐targeted agent sequential therapy: A propensity score‐matched analysis

Abstract: Aim The optimal choice between sorafenib (SOR) or lenvatinib (LEN) as the first‐line treatment for unresectable hepatocellular carcinoma (u‐HCC) remains debatable. Using propensity score matching, this study compares the outcomes of SOR and LEN in the molecular‐targeted agent (MTA) sequential treatment of u‐HCC patients. Methods This retrospective, multicenter, observational study recruited 137 u‐HCC patients who underwent primary treatment with LEN (n = 52) or SOR (n = 85) between June 2017 and June 2020 afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…Hepatic reserve function and portal vein invasion at treatment initiation are general prognostic factors for u‐HCC treatment with MTAs, 32,47 and they were also found to be prognostic factors in our study; however, the hepatic function was observed only in PFS and not in OS analysis. This may be due to the limitation of this study described below.…”
Section: Discussionsupporting
confidence: 45%
“…Hepatic reserve function and portal vein invasion at treatment initiation are general prognostic factors for u‐HCC treatment with MTAs, 32,47 and they were also found to be prognostic factors in our study; however, the hepatic function was observed only in PFS and not in OS analysis. This may be due to the limitation of this study described below.…”
Section: Discussionsupporting
confidence: 45%
“…Additionally, another study from Japan compared the clinical results of sorafenib and lenvatinib PSM. 25 However, that study included Child-Pugh class A cases alone. As our study aimed to reflect real-world data, we included Child-Pugh B patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the present study, 12.7% of the patients with HCC within up-to-seven criteria exhibited a decline in liver function from Child–Pugh class A to class B after TACE. Furthermore, previous studies have reported that the treatment efficiency of MTAs is associated with liver function [ 5 , 9 , 23 ] and that the use of MTAs improves the prognosis of advanced HCC compared with TACE [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that for patients with HCC beyond up-to-seven criteria [ 6 , 8 ], treatment with MTAs is recommended as the treatment efficiency of TACE for HCC beyond up-to-seven criteria is poor [ 6 ] and TACE increases the decline in liver function [ 5 , 6 ]. Other studies have reported that the treatment efficiency of MTAs depends on liver function [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%